2020
DOI: 10.1113/jp279919
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐gastrointestinal amyloid‐β1–42 oligomers perturb enteric function and induce Alzheimer's disease pathology

Abstract: Alzheimer's disease (AD) patients and transgenic mice have beta-amyloid (Aβ) aggregation in the gastrointestinal (GI) tract. r It is possible that Aβ from the periphery contributes to the load of Aβ in the brain, as Aβ has prion-like properties. r The present investigations demonstrate that Aβ injected into the GI tract of ICR mice is internalised into enteric cholinergic neurons; at 1 month, administration of Aβ into the body of the stomach and the proximal colon was observed to partly redistribute to the fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
80
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(90 citation statements)
references
References 45 publications
1
80
0
Order By: Relevance
“…Changes altering the gut microbiota can activate proinflammatory cytokines and increase intestinal permeability, which lead to the development of insulin resistance that is associated with AD [ 117 ] ( Figure 2 ). Interestingly, recent work has shown that AD development could start even in the gut and then spread to the brain [ 118 ]. In this study, the gastric wall of mice was injected with Aβ 1–42 oligomers.…”
Section: Gut Microbiota In Admentioning
confidence: 99%
See 1 more Smart Citation
“…Changes altering the gut microbiota can activate proinflammatory cytokines and increase intestinal permeability, which lead to the development of insulin resistance that is associated with AD [ 117 ] ( Figure 2 ). Interestingly, recent work has shown that AD development could start even in the gut and then spread to the brain [ 118 ]. In this study, the gastric wall of mice was injected with Aβ 1–42 oligomers.…”
Section: Gut Microbiota In Admentioning
confidence: 99%
“…Over 1 year, it was observed that the amyloid migrated from the intestine to the brain. Consequently, the translocation of Aβ oligomers from the gut to the brain can have a major contribution in causing AD and neuroinflammation [ 118 ].…”
Section: Gut Microbiota In Admentioning
confidence: 99%
“…Amyloid deposition in the vagus nerve and celiac ganglions has been reported in patients with systemic amyloidosis [ 171 ]. Recently, Sun et al showed that intra-GI injection of Aβ oligomers induced vagal and cerebral amyloidosis after 12 months [ 172 ], suggesting that neural transport may be considered as a potential route of spread of Aβ pathology towards the CNS.…”
Section: Roles Of Diet and Microbiota In Neurodegenerative Diseasementioning
confidence: 99%
“…In a recent issue of The Journal of Physiology , Sun et al . (2020) used a novel dementia mouse model to study the influence of gut Aβ on CNS histopathology and function. The model consisted of injecting Aβ oligomers (labelled or unlabelled) into the gut serosa of male Institute of Cancer Research mice, a strain widely used for disease modelling studies.…”
mentioning
confidence: 99%